THE DIELECTRIC CHARACTERISTICS OF 22 KV XLPE UNDERGROUND CABLES WITH DEGRADED ARTIFICIAL JOINT - Udomluksananon, Patt; Boonsaner, Nutthaphan; Wiangtong, Theerayod; Jeenmuang, Siwakorn; Chumpiboon, Komin; Dorkmai, Kritsada; Rojanasunan, Warisanan; Pattanadech, Norasage (My University, 2023)
This paper represents the dielectric characteristics of the 22 kV underground cable test specimen. Two 3 m XLPE underground cables were connected with the heat-shrinkable joint that has been simulated with some artificial defects. The healthy heat-shrinkable terminations are at both ends of the cable test specimen. For this research, the underground cables with the healthy joint, the joint with a copper powder contaminant on the XLPE surface, and the joint with an incision on the XLPE surface were prepared to perform the experiment. To compare the dielectric characteristics of the underground cables with the healthy joint and degraded artificial joints, the polarization and depolarization currents (PDC) measurements and the very low frequency-tangent delta (VLF-TD) testing, according to IEEE standard 400.2-2013, were conducted. From the PDC measurements, the test results are not clearly different for the underground cables with the defective joint when compared to the healthy joint case, except for the electrical conductivity and insulation resistance that show the difference between them. The VLF tangent delta parameters and mean tangent delta comparison curve show differences in each case, which can contribute to assessing the condition of the underground cable systems.
Keywords: DEGRADED JOINT; DIELECTRIC CHARACTERISTICS; POLARIZATION AND DEPOLARIZATION CURRENTS; VERY LOW FREQUENCY TESTING; XLPE UNDERGROUND CABLE